Majas Dalam Lirik Lagu Answer Karya Bump of Chicken: Kajian Stilistika - Ni Luh Yunda Anindyana; Made Henra Dwikarmawan Sudipa (KIRYOKU, 2022)
This research discusses the figure of speech in the lyrics of the song Answer by Bump of Chicken. The data used is obtained from the lyrics of the song by Bump of Chicken with the title Answer. The purpose of this research is to analyze the figure of speech and meaning contained in the lyrics of the song Answer. The theory used in the research is the stylistic theory of Burhan Nurgiyantoro (2019). The method and technique of data collection used is the literature study method while the data collection technique uses listening and recording techniques. The data analysis method used is descriptive method with qualitative techniques. The method of presenting the results of data analysis uses informal methods. The result of this research is 1 hyperbole, 1 personification, 1 metaphor, 2 similes, 1 repetition, and 1 allegory.